Secondary housing supply - Andreas Mense (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2023)
I estimate the impact of new housing supply on the local rent distribution, exploiting delays in housing completions caused by weather shocks during the construction phase. Increasing the flow of new supply by 1 percent lowers average rents by 0.2 percent, and increases disproportionately the number of second-hand units offered for rent. The impact of the supply shock is similarly strong in locations experiencing growing housing demand. Moreover, it affects the entire rent distribution. Employing a quantitative model, I explain this pattern by secondary supply: New supply triggers a cascade of moves that frees up units in all segments of the local market. – – Ich schätze die Auswirkungen des neuen Wohnungsangebots auf die lokale Mietpreisverteilung. Als Instrument nutze ich wetterbedingte Verzögerungen während der Bauphase. Eine Erhöhung des neuen Wohnungsangebots um 1 Prozent senkt den durchschnittlichen Mietpreis um 0,2 Prozent und erhöht überproportional die Zahl der zur Miete angebotenen Bestandswohnungen. Die Effekte des Angebotsschocks sind an Standorten mit wachsender Wohnungsnachfrage ähnlich stark, dieser wirkt sich außerdem auf die gesamte Mietpreisverteilung aus. Mithilfe eines quantitativen Modells lässt sich dieses Muster durch das sekundäre Angebot erklären: Der Wohnungsneubau löst eine Kaskade von Umzügen aus, durch die in allen Segmenten des lokalen Marktes Wohnungen frei werden.
Keywords: D15; D40; R21; R31; 330; housing supply; rental housing; rent distribution; secondary markets; market integration